LIFETIME EXERCISE IS ASSOCIATED WITH EUGONADISM IN AGING MEN: A PRELIMINARY INVESTIGATION - Lawrence D. Hayes,; Nicholas Sculthorpe,; Peter Herbert,; Fergal M. Grace, (Sport Scientific And Practical Aspects, 2025)
Testosterone is an important biological hormone, which displays a gradual decline with advancing age. Exercise training has been proposed as a first-line therapy for biochemical hypogonadism (clinically low serum testosterone). As such, the present investigation compared the incidence of biochemical hypogonadism (total testosterone <11.3 nmol·L-1) in a cohort of otherwise healthy lifelong sedentary men (SED [N=24], 63±5 years), compared with a positive control group of lifelong exercisers (LEX [N=16], 60±5 years) using electrochemiluminescent immunoassay. Fisher’s exact test identified significantly more of the SED group were classified as biochemically hypogonadal than the LEX group (8/24 compared to 2/16 respectively; p<.05). These data provide preliminary evidence that exercise may protect against the development of low testosterone defined hypogonadism in aging men.